2016
DOI: 10.1155/2016/7145708
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Undernutrition and Its Associated Factors among Children below Five Years of Age in Bure Town, West Gojjam Zone, Amhara National Regional State, Northwest Ethiopia

Abstract: Background. Malnutrition is the major public health problem over the world. Developing countries are highly affected. Asian and Sub-Saharan African countries, including Ethiopia, contribute the highest of all. The main aim of this study was to assess the prevalence of undernutrition and its associated factors among children below five years of age.Methods. Community-based cross-sectional survey was conducted on 342 study participants. Simple random sampling technique was used to select sampling kebeles and stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

23
60
6
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 21 publications
23
60
6
1
Order By: Relevance
“…In this study, the prevalence of severe stunting (22.9%) and underweight (10.3%) is markedly higher than the previous studies that reported 7.90% severely stunting and 3.20% severely underweight in Bure Town, west Gojjam Zone [17]. Children born in rural areas five years preceding the survey were more likely severely stunted (21.5%) and severely underweight (9.30%) than their urban counterparts.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…In this study, the prevalence of severe stunting (22.9%) and underweight (10.3%) is markedly higher than the previous studies that reported 7.90% severely stunting and 3.20% severely underweight in Bure Town, west Gojjam Zone [17]. Children born in rural areas five years preceding the survey were more likely severely stunted (21.5%) and severely underweight (9.30%) than their urban counterparts.…”
Section: Discussioncontrasting
confidence: 71%
“…Moreover, male children are highly severely stunted (27.3%) and severely underweight (12.2%) than females. is figure is higher than that reported in the study in the Bure Town of west Gojjam [17], 10.7% of severely stunted and 6% of severely underweight.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…These findings suggest that children in the capital city have a better nutritional status compared to other parts of the country. Stunted under five children in our study was much lower compared to other areas of the world like Ethiopia (57.5), [19] Philippines (34%), [16] North Vietnam (29.8%), [13] NW Ethiopia (24.9%), [12] and Thailand (19.9%). [20] This difference could be due to inclusion of children from the capital, Kathmandu and surrounding districts only.…”
mentioning
confidence: 54%
“…than that of 11.1% in NW Ethiopia, [13] but lower than that of Ethiopia (16%), [14] and North West Tanzania (17.8%). [15] Severely wasted population in this study was 6.36% which is higher than that in Philippines.…”
mentioning
confidence: 60%